2009
DOI: 10.1038/sc.2008.174
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study examining correlates of body image among women living with SCI

Abstract: Study design: Cross-sectional pilot study. Objectives: To explore correlates of body image among women with spinal cord injury (SCI), within the framework of Cash's cognitive behavioral model of body image. Setting: Hamilton, Ontario, Canada. Methods: Women with SCI (N ¼ 11, 64% with tetraplegia) reported their functional and appearance body image (Adult Body Satisfaction Questionnaire). A 3-day recall of leisure time physical activity (LTPA), three measures of body composition (that is, weight, waist circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…This finding corroborates earlier studies in the chronic phase, which shows, that over time, people with SCI seem to adjust to their changed bodies. 3,4,15,27 Our hypothesis that Alienation and Harmony would be associated with demographic variables was only partly confirmed. Associations between Alienation and Harmony and the injuryrelated variables were stronger.…”
Section: Insert Tablementioning
confidence: 73%
See 4 more Smart Citations
“…This finding corroborates earlier studies in the chronic phase, which shows, that over time, people with SCI seem to adjust to their changed bodies. 3,4,15,27 Our hypothesis that Alienation and Harmony would be associated with demographic variables was only partly confirmed. Associations between Alienation and Harmony and the injuryrelated variables were stronger.…”
Section: Insert Tablementioning
confidence: 73%
“…4,10,12,13 Other studies suggest that the satisfaction with the body improves over the years after SCI. 3,12,15 The age at injury does not seem to have any influence. 11 Some studies found that the satisfaction with appearance after SCI was not different from a reference group.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations